2012
DOI: 10.1002/hbm.22016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cortical network properties using TMS–EEG

Abstract: The past decade has seen significant developments in the concurrent use of transcranial magnetic stimulation (TMS) and electroencephalography (EEG) to directly assess cortical network properties such as excitability and connectivity in humans. New hardware solutions, improved EEG amplifier technology, and advanced data processing techniques have allowed substantial reduction of the TMS-induced artifact, which had previously rendered concurrent TMS-EEG impossible. Various physiological artifacts resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(175 citation statements)
references
References 160 publications
3
164
0
2
Order By: Relevance
“…TMS-EEG facilitates a direct assessment of the cortical response to stimulation, removing the confounding influence of variations in spinal cord excitability that are known to effect conventional MEP measurements. In addition, combining these two methods provides significantly more information about the local and global response to ppTMS than can be derived from the MEP [21,22]. For LICI, previous studies utilising TMS-EEG in M1 have identified cortical indices of inhibition within TMS-evoked EEG potentials (TEPs), with specific TEP peaks produced by the test stimulus being reduced in amplitude when a conditioning stimulus is applied 100 ms earlier [23].…”
Section: Introductionmentioning
confidence: 99%
“…TMS-EEG facilitates a direct assessment of the cortical response to stimulation, removing the confounding influence of variations in spinal cord excitability that are known to effect conventional MEP measurements. In addition, combining these two methods provides significantly more information about the local and global response to ppTMS than can be derived from the MEP [21,22]. For LICI, previous studies utilising TMS-EEG in M1 have identified cortical indices of inhibition within TMS-evoked EEG potentials (TEPs), with specific TEP peaks produced by the test stimulus being reduced in amplitude when a conditioning stimulus is applied 100 ms earlier [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of possible 'filtering' of cortico-spinal synapses and the motor endplate, a direct correlation between MEP amplitude and cortical excitability remains controversial. Accordingly, efforts are currently focusing on a more direct analysis of cortical inhibition, which is independent of the stimulated area of the cortex, using TMS-evoked electroencephalographic (EEG) potentials (Rogasch and Fitzgerald, 2013;Premoli et al, 2014). This attempt is supported by other techniques, e.g.…”
Section: Tms-based Assessment Of Inhibitory Cortical Networkmentioning
confidence: 99%
“…TEPs provide quantifiable markers of the cerebral neurophysiological state (Carlo Miniussi & Thut, 2010;Rogasch & Fitzgerald, 2013) and, in a similar fashion to MEPs, are influenced by TMS intensity (Kahkonen, Wilenius, Komssi, & Ilmoniemi, 2004;) and coil orientation (Bonato, Miniussi, & Rossini, 2006). While the amplitude of TEPs is greatest in the stimulated cortical area, it is possible to measure TEPs at cortical sites distant to the site of stimulation, potentially providing a useful measure of connectivity (Ilmoniemi et al, 1997;Kahkonen, Komssi, Wilenius, & Ilmoniemi, 2005;Komssi et al, 2002;Komssi et al, 2004).…”
Section: How Do We Investigate Nibs-induced Plasticity?mentioning
confidence: 99%